COMMUNICATION STRATEGIES IN THE CONVERSATIONS BETWEEN INDONESIAN UNIVERSITY STUDENTS AND A NATIVE SPEAKER - Farid Noor Romadlon (Vision: Journal for Language and Foreign Language Learning, 2016)
Practicing conversations or dialogues in various context or situation is as the essential aspect for students because it smoothen their skill in communication and their English mastery. Whenever people use language to interact, one of the things people are do- ing with it is establishing a relationship between them; between the speaker speaking now and the person who will probably speak next. It means, strategies in communicating put an important role to reach the goal of the interaction or the communication.This study is to identify the communication strategies of In- donesian university students, especially students of the English De- partment Education Faculty of Muria Kudus University and native speaker used in communication in natural conversation and to find out the possible factors cause the choice of  the strategies in the conversation. The method applied in this study is descriptive qualitative. The subjects of this study are fourth semester students of English De- partment of Muria Kudus University and one native speaker. The data were obtained by inviting and asking the students and the na- tive speaker to have a conversation for around one hour. Then, the conversation was recorded by using camera. The recorded data were transferred into the printed one as a script. The data analysis was conducted in several ways, among other transcribing the recorded data, identifying each utterance and displaying the result in the table, classifying the utterances based on the type of strategies, and inter- preting the communication or the conversation.The results showed that there were 306 turns in the conver- sation between the students and the native speaker. The types of strategies used in the conversations were Circumlocution (C) for 38.98 % (23), followed by Language Switch (LS) for 15.3 % (9) and Topic Avoidance (TA) for 14.6 % (8), Literal Translation (LT) for 6.8 % (4), Mime (M) for 8.5 % (5), Word Coinage (WC) and Mes- sage Abandonment (MA) for 6.8 % (4), Appeal for Assistance (AA) for 5.6 % (3), and Approximation (A) for 3.39 % (2). The last find- ing showed that there were two main factors that cause the choice of the strategies in the conversations. They were proficiency of the speaker and features of the communicative situation. In the use of communication strategies, both students of Eng- lish Department Muria Kudus University and the native speaker try to have a relative balance of power relation without the domination of one person to others. Some factors which cause the use of the strategies are lack of meaning, social use aspect, speech, voice, and fluency. To improve students’ strategies in communication, they should practice their English more, so their speaking and their strategies will be improved. Besides, lecturers also should apply the contextual teaching in which the environment and culture are inserted into the topic.